Evidence from financial freedom moderating the relationship between government intervention and financial stability - Duan, Chengyonghui; Soh, Wei Ni; Ong, Tze San; Abdul Rahim, Norhuda (Elsevier Ltd, 2025)
This article mainly explores the moderating effect of financial freedom on the effectiveness of government intervention in financial stability. To find more effective and accurate intervention measures, this article compares government intervention from two aspects: fiscal policy, represented by government spending and monetary policy, represented by monetary freedom. Financial stability is no longer a single stability standard but an overall multi-faceted stability, from the three dimensions of household savings, credit growth rate, and macro economy which is the deviation of GDP growth rate, from micro to macro measures of financial stability. This paper explores the moderating effect of financial institution efficiency on the effectiveness of government intervention through the micro-enterprise environment level. This article selects data from 136 countries worldwide and uses the system GMM model to verify the empirical results from 2016 to 2022. The results show that the interaction between financial freedom and government spending has a positive impact on household savings, a negative effect on credit growth rate, and a positive impact on the deviation of GDP growth rate. The interaction between financial freedom and monetary freedom positively impacts household savings, credit growth, and the GDP deviation. According to the marginal effect of the moderating variable financial freedom, the moderating effect of financial freedom on monetary freedom is stronger than that of government spending. Monetary policy is more effective than fiscal policy. In countries with a higher degree of financial freedom, fiscal policy has the most significant impact on the credit market, and monetary policy has the greatest impact on household savings environment. In summary, this study compares fiscal and monetary policy and studies the effects of financial freedom, which is the autonomy and efficiency of financial institutions. Different dimensions of financial stability through regulating fiscal policy and monetary policy based on the same long-term data. It aims to find the most effective, accurate, and influential government intervention methods and provide policy references and guidance for the country to implement effective interventions.